Caracterização nutricional e utilização de resíduos da Indústria alimentícia na dieta de frangos de corte. - Lira, Rosa Cavalcante (2018)
Three experiments had been carried out in which the first one was a metabolism test, by the traditional method, to evaluate the nutritional value of the passion fruit residue in different substitution levels in diet and in two broiler chicken ages. There was a significant difference between ages within all residue replacement levels. For AME, AMEn, CAMDM, MCCP and CAMGE the mean of chicken aged between 10 to 17 days was higher than those with age between 1 to 8 days within all levels of residue replacement. The second and third experiments aimed to evaluate the nutritional value of the biscuit residue with the same substitution levels and ages of the first experiment. It was observed that the older birds had higher mean values for AME, AMEn, CAMDM, MCCP and CAMGE at all levels of residue replacement. The fourth experiment aimed to evaluate the effect of the passion fruit residue on the broilers carcass performance and yield, 200 birds were distributed in a completely randomized experimental design with five treatments (0%, 4%, 8%, 12% and 16% inclusion of the residue in the diet) and four replicates of 10 birds.The residues inclusion levels influenced the consumption of feed at the ages of 1 to 7 days and 8 to 14 days. In the other periods the consumption was not affected. Weight gain where only affected in the first two weeks, with negative linear effects, in which at every 1% of inclusion the weight gain ration decrease 2.3875 g/ bird / week and 2.1830 g / bird / week, respectively, for the first and second week. Feed conversion worsened linearly up to 21 days and in the total period of 42 days. There was a negative influence of inclusion levels on absolute and relative thigh weight and positive for absolute and relative torso weight. There was no effect on the absolute weights and yields of the edible viscera. The passion fruit and biscuit residue presented better nutritional values at the age of 10 to 17 days, with good potential for its use in the broilers diet. Passion fruit residue can be used up to 16% inclusion in the diet in the period from 22 to 40 days of age without affecting the productive performance of broiler chickens and in the period from 1 to 42 days without damaging the carcass yield.